Remodeling the zonula adherens in response to tension and the role of afadin in this response - Choi, Wangsun; Acharya, Bipul R.; Peyret, Grégoire; Fardin, Marc Antoine; Mège, René Marc; Ladoux, Benoit; Yap, Alpha S.; Fanning, Alan S.; Peifer, Mark (The Journal of Cell Biology, 2016)
Morphogenesis requires dynamic coordination between cell-cell adhesion and the cytoskeleton to allow cells to change shape and move without losing tissue integrity. We used genetic tools and superresolution microscopy in a simple model epithelial cell line to define how the molecular architecture of cell-cell zonula adherens (ZA) is modified in response to elevated contractility, and how these cells maintain tissue integrity. We previously found that depleting zonula occludens 1 (ZO-1) family proteins in MDCK cells induces a highly organized contractile actomyosin array at the ZA. We find that ZO knockdown elevates contractility via a Shroom3/Rho-associated, coiled-coil containing protein kinase (ROCK) pathway. Our data suggest that each bicellular border is an independent contractile unit, with actin cables anchored end-on to cadherin complexes at tricellular junctions. Cells respond to elevated contractility by increasing junctional afadin. Although ZO/afadin knockdown did not prevent contractile array assembly, it dramatically altered cell shape and barrier function in response to elevated contractility. We propose that afadin acts as a robust protein scaffold that maintains ZA architecture at tricellular junctions.
CRIS-Team Scopus Importer:2024-02-19